Horizontal Deformation Monitoring of Kut Barrage-Iraq using High Precision GNSS& Total Station - Reham Riyad Mahmoud; Ghadah Hasan Mohammed (Tikrit Journal of Engineering Sciences, 2017)
The modern evaluation and analysis techniques for the horizontal deformation of concretestructures such as barrages depend on a geodetic network, with control points, required to carry out the adjustment for the networks according to the adjustment techniques "Least Squares method". The study included measurement of fourteen point in the downstream side, depending on the global satellite navigation system and using the Adjust program to calculate the amount of displacement resulting. A comparison done between the resulted deformations magnitude for the network points for 2014 epoch with respect to the General Directorate for Survey (GDS) at epoch 2005 the deformation or movement could be verified by applying the statistical techniques to analyze the movement. The analysis shows that the movement displacement systems stable and amount 3.5cm.